The Effect of Social Support on the Parents with Disabilities Children in Experiencing Stress: Literature Review - Fitria Dila Sari; Hema Malini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Having children with special needs requires parents to be more creative in their care, and it is not uncommon for parents to feel stressed. Many studies demonstrate that good social support is essential for developing parents' coping skills. This study aimed to investigate the impact of social support on the stress-coping of parents with children with disabilities. Methods: This study was a literature review. For relevant studies, articles were gathered from PubMed and Science Direct databases. The inclusion criteria were full-text papers that were free and in English; research was conducted on parents of children with disabilities; the article's content was relevant to the topic, and it was an original article published in the last seven years (2015-2021). There were five articles discovered that fulfilled the eligibility requirements. Results: The results showed that social support significantly impacts the development of parental coping strategies for dealing with challenges or stress experienced by parents of disabled children. Conclusions: This study concluded that offering adequate social support interventions to parents developed parental coping by being adaptive, allowing parents to overcome stress. The impact of this study influences how parents relate, behave, and care for their children, resulting in a favorable impact on their child's development.